Metal-oxide semiconductors for carbon monoxide (CO) gas sensing: A review. (March 2020) - Mahajan, Sunil; Jagtap, Shweta
Graphical abstract: Highlights: In this review recent progress on the development of different metal-oxide semiconductors (MOS) based nanostructure for carbon monoxide (CO) gas sensor is summarized. The commonly investigated classes of materials are MOSs (notably, ZnO, SnO2 and TiO2 ) are discussed as key oxides. Scope of many others including CeO2, In2 O3, WO3, CdO, CuO, composite oxides and YSZ also discussed. Various synthesis/fabrication methods such as CVD, hydrothermal, screen printing, sputtering, spray pyrolysis, sol-gel, co-precipitation method, electrospinning, pechini method, etc. are discussed with their advantages and Limitations. Effects of doping on the morphology of nanostructure and performance parameters of CO gas sensors were discussed. According to future perspectives MOSFET and graphene based gas sensors are also discussed with their properties, advantages and potential in gas sensing. Abstract: The development of metal-oxide semiconductor (MOS) based gas sensor has engrossed demanding research interest in the last several decades because of their potential for the selectivity, high sensitivity and fast detection of various toxic gases. Carbon monoxide (CO) is odorless, colorless and one of the most toxic gases. In this review recent progress on the development of different MOS based nanostructure for CO gas sensor is summarized. The commonly investigated classes of materials are MOSs (notably, zinc oxide and tin oxide) and yttrium stabilized zirconium. Recently, many metal oxide semiconductor including tin oxide, zinc oxide, titanium oxide, indium oxide, tungsten oxide, cerium oxide, copper oxide, composite MOS etc have been tested for CO gas sensing. The main focus is on new approaches for the synthesis of CO gas sensor by various researchers to improve the sensing performance like selectivity, sensitivity, response and recovery time with different materials and catalysts used.